Uma análise da cenografia e do ethos de trigger warnings em obras digitais - Marques, Isabela Herrera (Universidade Federal de São Carlos, 2025)
This undergraduate thesis investigates the use of trigger warnings in digital works, specifically in national books published on the Kindle platform. The research analyzes the enunciative scene of these warnings with the aim of understanding how this discourse organizes the relationship between author, text, and reader, influencing expectations and reading practices in the digital environment. Understood as preventive discursive markers, trigger warnings aim to alert readers to sensitive content such as violence, abuse, and self-harm. In independently published Kindle works, these warnings have become more frequent, as national authors use this resource to establish a pact of care and respond to ethical demands related to mental health. In light of French Discourse Analysis, more specifically the notions of Scenes of Enunciation and Ethos proposed by linguist and discourse theorist Dominique Maingueneau, the study shows that the trigger warning functions as a metadiscursive statement that precedes and reorganizes the main discourse, creating a scene marked by caution, care, and the negotiation of meaning. It is inferred that this resource shifts interpretative responsibility, reinforcing contemporary discourses on mental health, narrative responsibility, and inclusion. Thus, in national digital works on Kindle, trigger warnings act not only as protective mechanisms but also as emerging discursive practices supported by linguistic grounding and an ethics of care, ontributing to making readers feel more comfortable and prepared during the reading experience.
An analysis of the scenography and ethos of trigger warnings in digital books
Keywords: Trigger warnings; Cenas enunciativas; Análise do discurso; Ética do cuidado; Kindle; Trigger warnings; Enunciative scenes; Discourse analysis; Ethics of care; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; 4. Educação de Qualidade